2017
DOI: 10.1007/s12663-017-1011-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Multimodal Therapy in the Survival Outcomes of Advanced-Stage (Stage III–Stage IV) Oral Carcinoma Patients: An Institutional Experience in Asian Indian Population

Abstract: Aim Primary ablative surgery followed by post-op radiotherapy (S-RT) remains the mainstay of treatment for stage IIIstage IV oral carcinoma. A retrospective analysis of survival rates of advanced-stage OSCC patients treated with multimodal therapies (S-RT or combined chemoradiation) was performed to analyse the outcome for patient survival and whether addition of adjuvant chemotherapy (S-CRT) improves survival. Materials and Methods Demographic, pathological, treatment and follow-up data of 128 patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In our previous study, we reported AuNRs were synthesized in the cavity of hollow silica nanoparticles to construct rattle-structured rough nanocapsules, which were used for complementary gene/chemo/photo therapy and play a high-efficiency anti-tumor effect [ 45 ]. Multimodal combination therapy has also been extensively studied in oral tumors [ [197] , [198] , [199] ]. AuNPs have become a promising platform for the diagnosis and treatment of nanomedicine with multiple therapeutic and diagnostic functions [ [200] , [201] , [202] , [203] ].…”
Section: Application In Oral Cancer Treatmentmentioning
confidence: 99%
“…In our previous study, we reported AuNRs were synthesized in the cavity of hollow silica nanoparticles to construct rattle-structured rough nanocapsules, which were used for complementary gene/chemo/photo therapy and play a high-efficiency anti-tumor effect [ 45 ]. Multimodal combination therapy has also been extensively studied in oral tumors [ [197] , [198] , [199] ]. AuNPs have become a promising platform for the diagnosis and treatment of nanomedicine with multiple therapeutic and diagnostic functions [ [200] , [201] , [202] , [203] ].…”
Section: Application In Oral Cancer Treatmentmentioning
confidence: 99%